2018
DOI: 10.1038/s41467-018-05061-3
|View full text |Cite
|
Sign up to set email alerts
|

Rapid transport of deformation-tuned nanoparticles across biological hydrogels and cellular barriers

Abstract: To optimally penetrate biological hydrogels such as mucus and the tumor interstitial matrix, nanoparticles (NPs) require physicochemical properties that would typically preclude cellular uptake, resulting in inefficient drug delivery. Here, we demonstrate that (poly(lactic-co-glycolic acid) (PLGA) core)-(lipid shell) NPs with moderate rigidity display enhanced diffusivity through mucus compared with some synthetic mucus penetration particles (MPPs), achieving a mucosal and tumor penetrating capability superior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
179
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 217 publications
(188 citation statements)
references
References 44 publications
1
179
0
3
Order By: Relevance
“…In contrast, I‐PPNTs deeply penetrated into the tumor tissue and diffused throughout the tumor sections, implying the superior tumor penetrating ability of PBA‐functionalized PNTs. This would be most likely explained by rotation‐facilitated deep tumor penetration of rod‐shaped nanoparticles as reported by Gao and coworkers . Noticeably, the red fluorescence of ICG and green fluorescence of GFP colocalized well in the I‐PPNT‐treated tumor sections, implying highly efficient internalization of the peptide nanotubes.…”
Section: Resultssupporting
confidence: 64%
“…In contrast, I‐PPNTs deeply penetrated into the tumor tissue and diffused throughout the tumor sections, implying the superior tumor penetrating ability of PBA‐functionalized PNTs. This would be most likely explained by rotation‐facilitated deep tumor penetration of rod‐shaped nanoparticles as reported by Gao and coworkers . Noticeably, the red fluorescence of ICG and green fluorescence of GFP colocalized well in the I‐PPNT‐treated tumor sections, implying highly efficient internalization of the peptide nanotubes.…”
Section: Resultssupporting
confidence: 64%
“…Inserting the latter equation into Eq. (20) and setting the left-hand side to zero, the steady-state distance separating the self-driven particle from the central particles is given by…”
Section: A Evolution Of the Membrane Particlesmentioning
confidence: 99%
“…Considerable research advances have been made over the last few years in understanding the penetration of particles into cell membranes. Previous studies have shown that the particle uptake by living cells is strongly affected by the particle properties [20][21][22][23][24] and the physicochemical and functional properties of the membrane [25][26][27][28][29][30] .…”
Section: Introductionmentioning
confidence: 99%
“…The potential of such motors has been demonstrated in emerging applications like drug delivery, precision surgery, and environmental remediation. [ 1,3,4,10–16 ]…”
Section: Introductionmentioning
confidence: 99%